Reuse of Selected Lignocellulosic and Processed Biomasses as Sustainable Sources for the Fabrication of Nanocellulose via Ni(II)-Catalyzed Hydrolysis Approach: A Comparative Study - Yahya, Mazlita; Chen, You Wei; Lee, Hwei Voon; Hassan, Wan Hasamudin Wan (Springer, 2018)
This study investigates for the first time the feasibility of isolating nanocellulose from several selected feedstocks via a novel Ni(II)-hydrolysis process, including lignocellulosic biomasses (oil palm trunk, banana peel and coconut husk) and processed biomasses (newspaper, tissue paper and cotton linter), with an obtained gravimetric yield ranging from 59.6 to 86.2%. The isolation of nanocellulose products from these selected feedstocks was verified by the successive removal of most of their non-cellulosic components (lignin and hemicellulose) and cellulose amorphous regions, the increase in the crystallinity index and the nanoscale of the individual crystals. Most importantly, the resultant nanocellulose products rendered better thermal stability than that of corresponding original sources, which are highly potential to be utilized as the new renewable sources of reinforcement materials with potential applications in bio-nanocomposites and thermoplastics. Therefore, this work proves the viability of direct production of nanocellulose from a variety of cellulosic sources by using Ni(II)-based transition metal salt catalyst. The results suggested that the concept of waste to wealth could be well executed from the obtained nanocellulose, which are greatly potential for various industrial applications.